Perbandingan Komposisi Giblet Beberapa Jenis Itik Pada Pemeliharaan Semi Intensif - Muntia, La Ode; Hafid, Harapin; Napirah, Astriana (Jurnal Riset Multidisiplin Agrisosco, 2024)
The purpose of this study was to determine the carcass composition of several different types of ducks in a semi-intensive maintenance system. There were 16 ducks used with 3 months of age based on a complete randomized design (CRD) with 4 different duck treatments and 4 replications. Based on the results and discussion, it can be concluded that at the same age, Peking duck, alabio duck, manila duck and mojosari duck were significantly different (P <0.01) in cutting weight, carcass percentage, thigh percentage, back percentage, gizzard percentage and fat percentage abdominal. Meanwhile, the different types of ducks did not affect (P> 0.05) chest percentage, wing percentage, neck percentage and heart percentage. In general, live weight, percentage of carcasses and parts of carcasses of manila ducks were superior to mojosari ducks, alabio ducks and Peking ducks. The alabio duck is superior to the Peking duck and the mojosari duck. In terms of non-carcass organs, mojosari ducks had a percentage of gizzard superior to Peking, alabio and manila ducks, while the percentage of liver was significantly different (P <0.05) and the percentage of heart was not significantly different (P> 0.05). The abdominal fat content of alabio duck is very different from that of Peking duck, mojsari duck and manila duck.